Fragment of a Torana (decorative gateway or archway) - Temples of India Project Team (Jio Institute, 2024)
Seen here is a fragment of a torana (decorative gateway or archway) consisting of three bays made out of four pillars. One of the bays has the makara (crocodile-like mythical creature) torana intact. The octagonal pillars have kirtimukha (face of glory) bands and floral motifs. There are figures on the base of the pillars. It stands on a plinth made up of four mouldings. Framed divinity figures are found on the pillar. The remnant portion of this torana indicates that there was a gateway probably attached to it.